Pengaruh Konsumsi Rumah Tangga, Investasi Asing dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia - Ridha, Ahmad; Ismanidar, Nur; Iskandar, Iskandar; Asnidar, Asnidar (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study examines the dynamic relationship between economic growth, household consumption, foreign investment, and inflation in Indonesia using the Autoregressive Distributed Lag (ARDL) model approach. Empirical results show that household consumption and foreign investment significantly affect national economic growth in the short term. Meanwhile, inflation has an adverse effect on economic growth in the short term. In a long-term analysis, household consumption has a positive and significant effect compared to other variables at a significance level of 1%. In comparison, foreign investment has a positive effect at a significance level of 10%. The inflation variable in the long term does not have a significant effect on economic growth. This empirical finding shows that household consumption is still adequate and is one of Indonesia's main drivers of stimulating economic growth. This study has limitations in the form of time series data analyzed. It can use panel data and other actual variables for further research development.